Ergogenic effects of a 10-day L-citrulline supplementation on time to exhaustion and cardiorespiratory and metabolic responses in healthy individuals: a double-blind, randomised, placebo-controlled crossover trial - Schierbauer, J.; Francis, L.; Greco, F.; Zimmermann, P.; Moser, O. (Frontiers in Sports and Active Living, 2025)
IntroductionL-Citrulline supplementation has been a topic of debate due to its potential to augment L-arginine bioavailability and nitric oxide production. However, it remains uncertain whether it can truly serve as an ergogenic aid in endurance exercise performance. While it was previously recommended to include higher continuous doses of L-citrulline over ≥7 days, this study aimed to investigate whether a relative dosing strategy using 100 mg·kg−1 per day over 10 days could improve time to exhaustion (TTE) in healthy young adults.MethodsTwenty healthy, moderately active adult participants (nine females; age, 24.4 ± 0.9 years; BMI, 24.0 ± 2.5 kg·m−2; V̇O2max, 43.5 ± 6.3 mL·min−1·kg−1) received either 100 mg·kg−1 per day of L-citrulline (CIT) or a placebo (PLA) for 10 days in a double-blind, randomised, placebo-controlled crossover trial, before they performed two TTE tests at 5% above the second lactate turnpoint (LTP2). Cardiac output (Q̇), oxygen uptake (V̇O2), blood glucose ([Glu−]) and lactate concentrations ([La−]), and rating of perceived exertion (RPE) were quantified during each test.ResultsThere was no statistically significant difference in TTE between the trial arms (CIT vs. PLA: 20.5 ± 7.3 vs. 19.8 ± 5.7 min, p = 0.43). However, a trend was observed in the female subgroup (24.4 ± 6.2 vs. 21.9 ± 4.8 min, p = 0.06). Cardiac output (Q̇) also did not show significant differences between mean (CIT, 18.3 ± 3.7 L·min−1; PLA, 19.0 ± 4.5 L·min−1; p = 0.40) and maximum values (CIT, 28.7 ± 5.7 L·min−1; PLA, 26.6 ± 4.9 L·min−1; p = 0.22) in both trial arms. Mean V̇O2 was 1.77 ± 0.28 and 1.84 ± 0.25 L·min−1 (p = 0.06) for CIT and PLA, respectively. Similarly, mean maximum systolic (165 ± 17 vs. 171 ± 18 mmHg, p = 0.23) and diastolic (81 ± 6 vs. 83 ± 6 mmHg, p = 0.19) blood pressure levels were not significantly different between CIT and PLA trial arms.DiscussionHigher continuous doses of L-citrulline over 10 days do not increase TTE in healthy, moderately active individuals when compared with a placebo. Therefore, it is reasonable to assume that L-citrulline does not offer an ergogenic benefit for endurance performance. However, future research may focus on female populations or exercise protocols that involve longer distances to simulate competition.